2018
DOI: 10.14744/semb.2018.55376
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity profiles among patients with autoimmune bullous diseases; a retrospective study

Abstract: Objectives: The purpose of the present study was to define the accompanying diseases of patients with autoimmune bullous diseases (ABDs). Methods: One hundred forty-two patients with ABD who were followed up in the dermatology and venereology inpatient clinic of Şişli Hamidiye Etfal Training and Research Hospital between January 1999 and December 2015 were enrolled in the study. Age, gender, and accompanying diseases of the participants were recorded and compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…Of the 282 studies identified, a total of 16 studies with eleven case-control studies [15][16][17][18][19][20][21][22][23][24][25], three cohort studies [26][27][28], and two studies using both cohort and case-control designs [29,30] involving 637,285 patients met the inclusion criteria. The studies presented the association between BP and psychiatric disorders by reporting the scores of the Hospital Anxiety Depression Scale or applying the inpatient hospitalizations, as the case and control group were excluded from the quantitative synthesis [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 282 studies identified, a total of 16 studies with eleven case-control studies [15][16][17][18][19][20][21][22][23][24][25], three cohort studies [26][27][28], and two studies using both cohort and case-control designs [29,30] involving 637,285 patients met the inclusion criteria. The studies presented the association between BP and psychiatric disorders by reporting the scores of the Hospital Anxiety Depression Scale or applying the inpatient hospitalizations, as the case and control group were excluded from the quantitative synthesis [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…Many previous studies have shown associations between BP and cardiovascular risk factors, suggesting a possible link between BP and MS. During the past decade, a number of case–control studies 9 , 10 , 19 22 have shown a strong association between BP and diabetes, whereas others have not. 23 28 Similarly, hypertension has been shown to be significantly associated with BP in many case–control studies, 19 24 , 29 but not under all circumstances. 9 , 10 , 25 27 A few studies have shown a negative association between hyperlipidemia and BP, 24 but others have not shown any relationship.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 , 25 27 A few studies have shown a negative association between hyperlipidemia and BP, 24 but others have not shown any relationship. 19 , 21 In addition, two large population-based studies conducted in the United States showed a significant association between obesity and BP. 10 , 22 However, the use of medication before a diagnosis of BP and the treatment of BP with glucocorticoids or immunosuppressants may confound the relationship between components of MS and BP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Von den 282 identifizierten Studien erfüllten insgesamt 16 Studien, elf Fall-Kontroll-Studien [15][16][17][18][19][20][21][22][23][24][25], drei Kohortenstudien [26][27][28] und zwei Studien, die sowohl als Kohortenals auch als Fall-Kontroll-Studie konzipiert waren [29,30], mit 637 285 Patienten die Einschlusskriterien. Die Studien beschrieben den Zusammenhang zwischen BP und psychiatrischen Erkrankungen, indem sie die Werte der Hospital Anxiety Depression Scale dokumentierten oder die stationären Klinikaufnahmen anwendeten, wobei die Fall-und Kontrollgruppen von der quantitativen Synthese ausgeschlossen wurden [19,20].…”
Section: Ergebnisseunclassified